Assessing the Feasibility of Providing a Real-Time Response to Seizures Detected With Continuous Long-Term Neonatal Electroencephalography Monitoring. Issue 1 (January 2019) - Sharpe, Cynthia; Davis, Suzanne L; Reiner, Gail E.; Lee, Lilly I; Gold, Jeff J; Nespeca, Mark; Wang, Sonya G; Joe, Priscilla; Kuperman, Rachel; Gardner, Marissa; Honold, Jose; Lane, Brian; et al.
Abstract : Purpose: Continuous video electroencephalography (cEEG) monitoring is the recommended gold standard of care for at-risk neonates but is not available in many Neonatal Intensive Care Units (NICUs). To conduct a randomized treatment trial of levetiracetam for the first-line treatment of neonatal seizures (the NEOLEV2 trial), we developed a monitoring infrastructure at five NICUs, implementing recent technological advancements to provide continuous video EEG monitoring and real-time response to seizure detection. Here, we report on the feasibility of providing this level of care. Methods: Twenty-five key informant interviews were conducted with study neurologists, neonatologists, coordinators, and EEG technicians from the commercial EEG monitoring company Corticare. A general inductive approach was used to analyze these qualitative data. Results: A robust infrastructure for continuous video EEG monitoring, remote review, and real-time seizure detection was established at all sites. At the time of this survey, 260 babies had been recruited and monitored for 2 to 6 days. The EEG technician review by the commercial EEG monitoring company was reassuring to families and neonatologists and led to earlier detection of seizures but did not reduce work load for neurologists. Neurologists found the automated neonatal seizure detector algorithm provided by the EEG software company Persyst useful, but the accuracy of the algorithm was not such that it could be used without review by human expert. Placement of EEG electrodes to initiate monitoring, especially after hours, remains problematic. Conclusions: Technological advancements have made it possible to provide at-risk neonates with continuous video EEG monitoring, real-time detection of and response to seizures. However, this standard of care remains unfeasible in usual clinical practice. Chief obstacles remain starting a recording and resourcing the real-time specialist review of suspect seizures. Abstract : Supplemental Digital Content is Available in the Text.